Gopi diaries : Finding love - Murty, Sudha; Prabhat, Sandhya (Noida, Uttar Pradesh, India : HarperCollinsChildren's Books, an imprint of Harper Collins Publishers, 2021)
Story of a dog called Gopi and the loving human family that adopts him.
Happy birthday to me! -- Life's a dream -- A day at the office -- We are family -- Love, at last! -- Acknowledgements.
Children's story.
"The Gopi diaries is a series of three books for children. Coming home is the first book in the series. Finding love is the second"--Cover page 4.
Also available as an ebook.
Keywords: Dogs -- Juvenile fiction; Pets -- Juvenile fiction; Children's stories, English